Authentic Assessment in Qur’anic Studies: A Multidimensional Approach to Developing Higher-Order Thinking Skills in Islamic Higher Education - Devi Faizah Yuliana; Rusydi AM; Remiswal Remiswal; Juli Sardi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2026)
Higher-Order Thinking Skills (HOTS) have become an essential learning outcome in higher education, including Qur'anic studies, where students are expected to interpret religious texts in their contexts critically. However, assessment practices in many Qur'anic learning settings continue to emphasize knowledge acquisition rather than the integrated development of cognitive, psychomotor, and affective competencies. This study examined the contribution of a multidimensional authentic assessment approach to fostering students' HOTS in Qur'anic studies. A mixed-methods sequential explanatory design was employed. The study was conducted at the Faculty of Ushuluddin and Islamic Studies, UIN Imam Bonjol Padang, Indonesia, involving 50 undergraduate students enrolled in the Uṣūl al-Tafsīr wa Qawāʿiduhu course. Quantitative data were analyzed using multiple linear regression, while qualitative interview data were analyzed through thematic analysis to explain the statistical findings. The results showed that cognitive, psychomotor, and affective domains collectively made a significant contribution to HOTS. Among these domains, psychomotor engagement emerged as the strongest predictor, indicating that performance-based learning activities such as presentations, academic writing, and interpretive discussions play a central role in the development of higher-order thinking. The qualitative findings further revealed that conceptual understanding, active knowledge application, and reflective engagement operate as complementary processes that strengthen students' analytical and evaluative thinking. These findings suggest that authentic assessment should be viewed not merely as a means of evaluating learning outcomes but as an instructional approach that integrates knowledge, practice, and reflection to promote higher-order thinking. The study contributes to the growing body of research on authentic assessment by providing empirical evidence from the context of Islamic higher education and offering a multidimensional framework for enhancing HOTS in Qur'anic learning